PENGATURAN BATAS KETINGGIAN BANGUNAN DALAM MENJAGA KEBERLANJUTAN BENTANG ALAM DAN LINGKUNGAN TERBANGUN - Gusti Ayu Made Suartika (Bumi Lestari Journal of Environment, 2010)
This article attempts to relate two important issues of regulating building height limit and sustainability of the natural environment. It is part of publications that document findings resulted from the so called fundamental research study, that was consecutively funded by the Indonesian Department of Education in 2008 and 2009. This study used hermeneutical research approach, which was observed through selective case studies. Within the last two decades, sustainability of our nature and life on earth have attracted a serious attention, not only from environmentalists, but also from economists, politicians, academics, as well as those who concern about socio-cultural development as a whole. In line with the intense environmental destruction\'s taking place in a speed which has never been anticipated, this aforementioned condition continues to require intensive actions. Architecture and regional planning, two disciplines that dedicate their focus of interests on building design and the management of spatial development, cannot turn their eyes away from such a world-widely spread phenomenon. Both disciplines utilize space – nature –, which consequently bring about impacts on the surrounding environment. In relation to local development, planning discipline especially, orients its activities toward developing various mechanisms in guiding and controlling development, as well as sanctioning violations of planning laws. Ideally, these attributes aim at balancing spatial need of numerous interests, mitigating potential negative impacts on the environments, and offering solutions in overcoming problems and conflicts. Contextualizing its discussions within the above circumstances, this article investigates three prominent topics of discussion. First, it examines the idea of development and sustainability. Second, it studies the implementation of sustainability to the context of spatial development. Third, it bridges the first and second sections with the issue of building height limit regulation at a global level. Before embarking on discussion over these three elements, this article draws an emphasis on the inextricable correlations between sustainable development, spatial development, and building height. Overall, this article critically summaries considerations and efforts in sustaining our life on earth by appropriately addressing considerations of either limiting or relaxing building height limit in a particular planned area.